HADITH DAN SEJARAH: PENCARIAN TERHADAP SEJARAH ISLAM YANG OTENTIK - Khairul Amal (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2020)
This paper attempts to discuss the proper methodology in search for the authentic Islamic History. It discusses the relationship between two sister-disciplines, i.e. ?ad?th and History, their likenesses, many problems which the historians of Early Islam have to face in their research and the possibility of employing unique methodology of the study of ?ad?th on the study of Early Islamic History. The paper benefits from a plethora of monographs written by contemporary scholars of Islamic Studies. I conclude that Isn?d-cum-Matn Analysis developed separately by Gregor Schoeler and Harald Motzki seems promising for the study of Early Islam.This paper attempts to discuss the proper methodology in search for the authentic Islamic History. It discusses the relationship between two sister-disciplines, i.e. ?ad?th and History, their likenesses, many problems which the historians of Early Islam have to face in their research and the possibility of employing unique methodology of the study of ?ad?th on the study of Early Islamic History. The paper benefits from a plethora of monographs written by contemporary scholars of Islamic Studies. I conclude that Isn?d-cum-Matn Analysis developed separately by Gregor Schoeler and Harald Motzki seems promising for the study of Early Islam.